TINGKAT KEMAMPUAN REFLEKSI DIRI DALAM PEMBELAJARAN MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS TARUMANAGARA - Made Made Ayu Adesty Cahya Puspita (Journal Medical Universitas muhammadiyah Makassar, 2023)
Self-reflection is one of the important components needed by a learner to be able to develop himself. In medical education, self-reflection is useful in preparing students to become professional doctors and ready for lifelong learning. This study aims to determine the level of self-reflection ability in student learning at the Faculty of Medicine, Tarumanagara University by using a reflection in learning scale questionnaire. This research is descriptive quantitative with a cross-sectional approach. Respondents were 148 people with 74 students at the academic stage and 74 students at the professional stage. The results showed that the highest self-reflection ability in learning was owned by the academic stage respondents, was mostly at the level of the